Tissue level reactions in Catla catla(Hamilton-Buchanan), due to trichodinid ciliophoran, Tripartiella sp. infections - Acharya, Subhendu; Datta, Tanusree (Indian Journal of Fisheries, 2011)
Tissue level reactions in Catla catla(Hamilton-Buchanan), due to trichodinid ciliophoran, Tripartiella sp. infections